2021
DOI: 10.1038/s41419-021-03508-y
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 attenuates sepsis-induced acute kidney injury via Beclin1 deacetylation-mediated autophagy activation

Abstract: Our previous studies showed that silent mating-type information regulation 2 homologue-1 (SIRT1, a deacetylase) upregulation could attenuate sepsis-induced acute kidney injury (SAKI). Upregulated SIRT1 can deacetylate certain autophagy-related proteins (Beclin1, Atg5, Atg7 and LC3) in vitro. However, it remains unclear whether the beneficial effect of SIRT1 is related to autophagy induction and the underlying mechanism of this effect is also unknown. In the present study, caecal ligation and puncture (CLP)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 35 publications
2
64
0
Order By: Relevance
“…We found that the expression of autophagy-related protein LC3II increased gradually and peaked at 8 h, returned to baseline by 24 h. In contrast, p62 (SQSTM1, a mediator of cargo selection and an autophagic substrate) expression reached the lowest levels at 8 h with LPS treatment (Supplementary Figures 1A-C), which was consistent with the autophagosomes analysis in CLP-induced septic mouse model. Similar changes of LC3II and p62 have been reported in CLP model in our previous study (15).…”
Section: Autophagy Inhibition Precedes Apoptosis In Rtecs Following Sepsissupporting
confidence: 90%
See 3 more Smart Citations
“…We found that the expression of autophagy-related protein LC3II increased gradually and peaked at 8 h, returned to baseline by 24 h. In contrast, p62 (SQSTM1, a mediator of cargo selection and an autophagic substrate) expression reached the lowest levels at 8 h with LPS treatment (Supplementary Figures 1A-C), which was consistent with the autophagosomes analysis in CLP-induced septic mouse model. Similar changes of LC3II and p62 have been reported in CLP model in our previous study (15).…”
Section: Autophagy Inhibition Precedes Apoptosis In Rtecs Following Sepsissupporting
confidence: 90%
“…Different from the final result of cell death caused by apoptosis, activated autophagy plays a renal protective role by preventing apoptosis, preserving the mitochondrial functions, and maintaining the balance between the productions of proand anti-inflammatory cytokines (22). Our previous research has confirmed the above phenomena and verified that autophagy activation could reduce SAKI (15). The role of p53 in SAKI is rarely reported, although previous studies have explored the damaging role of p53 in bilateral renal ischemia-reperfusion induced AKI and cisplatin nephrotoxic AKI (27,28).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…SIRT1 can induce autophagy by directly deacetylating autophagy-related 5, 7, 8 genes ( Lee et al, 2008) , and forming deacetylated Atg5, Atg7, and Atg8. SIRT1 activation can also induce autophagy by promoting the deacetylation of Beclin1 at K430 and K437 ( Deng et al, 2021 ). Oxidative stress is closely associated with cisplatin-induced AKI; in cisplatin-induced AKI, kidney damage caused by cisplatin reduces the number and function of mitochondria and increases the production of ROS.…”
Section: Class III Histone Deacetylases and Acute Kidney Injurymentioning
confidence: 99%